Preliminary findings on electrically evoked cortical auditory potentials in cochlear implant recipients with inner ear malformations - Konting, Siti Hufaidah; Abu Bakar, Zulkiflee; Narayanan, Prepageran; Dzulkarnain, Ahmad Aidil Arafat (Thieme Medical Publishers, Inc., 2025)
Inner ear malformations (IEMs) represent unique challenges in cochlear implantation, potentially influencing electrode placement during surgery and neural responsiveness. Thus, electrically evoked cortical auditory potentials (eCAEPs) were suggested to be performed as objective measures of higher-level auditory perception at the cortical level in assessing cochlear implant (CI) outcomes in this complex population. This study aims to evaluate preliminary findings of P1 latency in eCAEPs among CI recipients with several types of IEMs at different positions of electrodes, that is, apical, medial, and basal regions. A cohort of five CI recipients with IEMs was evaluated using postopera- tive eCAEPs recordings, and P1 latency was analyzed at different positions of electrodes. The mean age of the subjects was 14.01 5.51 years, with common cavity malformations, incomplete partition type I (IP-I), incomplete partition type II (IP-II), and enlarged vestibular aqueduct. Early data suggest P1 responses were generally present in all IEM cases in this cohort, with the mean of P1 latency for the electrode at apical, medial, and basal regions of 108.2 13.4, 124.0 23.6, and 140.0 41.5 ms, respectively. These findings may reflect differential cortical response across IEM types at multiple CI electrode locations.